Práticas de leitura em aulas de história: um estudo de caso etnográfico - Luisa Teixeira Andrade Pinho (2013)
This research aim was to investigate the reading practices of History texts instituted in the context of a fifth grade History classroom of the Public Elementary School Eleonora Pierucetti of the City of Belo Horizonte Educational Network. We intend to answer the following question: How reading of History texts was socially accomplish in the referred classroom? The theoretical and methodological principles that guide this investigation are founded on a contemporary trend for classroom interactions analysis: the Interactional Ethnography. This approach is informed by an understanding of the central role of discourse in mediating processes of meaning construction in the classroom (Bloome and Bailey, 1992; Bloome and Egan-Robertson, 1993; Collins and Green, 1992; Gee and Green, 1998; Santa Barbara Classroom Discourse Group, 1992). From this perspective, we search to understand how Reading of History texts was discursively constructed by the members throught their interactions, verbal or non-verbal, and how these constructions influenced the opportunities available to students of reading and learning History in the observed classroom. The methodological procedures included video recording; field notes; materials collected during the observation such as students workbooks, tests and texts ; the analysis of the institution; interviews with the teacher and some students; and a prolonged field immersion period. Therefore, we followed, under the ethnographic perspective, a fifth grade History classroom for a year in 2010, observing the daily life of the classroom.